Impact of Back up Quantity Contract on Two-level Supply Chain: A Simulation Approach - Asif Muzaffar; Shiming Deng (International Journal of Supply Chain Management, 2013)
In this new era of Supply chain coordination contracts are offered and accepted according to the varying need and specification of the industry and business in discussion. The contract variations arise according to the circumstances and adaptability by both manufacturer and retailer. An important challenge faced by the contracts being offered is the adaptability and robustness when demand observed is different from the forecast. Because of stochastic and uncertain demand, retailer faces lost sales and eventually loses revenue within the same horizon. This paper discusses a back up quantity contract for a single season in which retailer orders for one-shot inventory ordering. Manufacturer retains some part of the ordered inventory as backup and provides the units at first stage. If stock at retailer lags behind the demand, he gets the backup quantity otherwise he pays some agreed upon nominal price to manufacturer in case that inventory is not at all required. We assumed the case of single manufacturer and single retailer. If units are not required, the risk of holding inventory lies with manufacturer and salvaged at zero. The strategy is suitable for businesses having short seasonal products and high demand variability. We used Monte Carlo simulation for analyzing lost sales and supply chain profit scenario and used worst case distribution and normal distribution to validate the Pareto improving contractual relationship.